Awesome blossom : - Myracle, Lauren (Amulet Books, 2013)
Katie-Rose, Milla, Yasaman, and Violet are happy to be a flower-friend foursome—until a new girl, Hayley, comes to school. Hayley is confident and mysterious and keeps the girls guessing. Katie-Rose worries she’s just another Evil Chick, but Violet befriends Hayley and hopes the girls can make room for her in their group. Meanwhile, love is in the air as Milla works up the courage to go on an actual date with the adorable Max, and Katie-Rose receives ten plush hedgehogs from a secret admirer. Even quiet Yasaman gets tangled in the drama when she opens a note from Ms. Perez to Mr. Emerson and realizes it’s—dun dun dun!—a love letter. Full of juicy secrets, budding romance, and—of course— flower friendship, Awesome Blossom is a fun and satisfying conclusion to the Flower Power series that once again proves Lauren Myracle “has her finger firmly on the pulse of tween girldom” (Booklist).